Collective Trauma and the Social Construction of Meaning - Hirschberger, Gilad (Frontiers in Psychology, 2018)
Collective trauma is a cataclysmic event that shatters the basic fabric of society. Aside from the horrific loss of life, collective trauma is also a crisis of meaning. The current paper systematically delineates the process that begins with a collective trauma, transforms into a collective memory, and culminates in a system of meaning that allows groups to redefine who they are and where they are going. For victims, the memory of trauma may be adaptive for group survival, but also elevates existential threat, which prompts a search for meaning, and the construction of a trans-generational collective self. For perpetrators, the memory of trauma poses a threat to collective identity that may be addressed by denying history, minimizing culpability for wrongdoing, transforming the memory of the event, closing the door on history, or accepting responsibility. The acknowledgement of responsibility often comes with disidentification from the group. The dissonance between historical crimes and the need to uphold a positive image of the group may be resolved, however, in another manner; it may prompt the creation of a new group narrative that acknowledges the crime and uses it as a backdrop to accentuate the current positive actions of the group. For both victims and perpetrators, deriving meaning from trauma is an ongoing process that is continuously negotiated within groups and between groups; it is responsible for debates over memory, but also holds the promise of providing a basis for intergroup understanding.